2016
DOI: 10.1016/j.jhep.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Removal of acetaminophen protein adducts by autophagy protects against acetaminophen-induced liver injury in mice

Abstract: Background & Aims Acetaminophen (APAP)-induced liver injury is the most frequent cause of acute liver failure in the US and many other countries. Metabolism of APAP results in formation of APAP protein adducts (APAP-AD) in hepatocytes and triggers mitochondrial dysfunction and necrosis. However, the mechanisms for how APAP-AD are removed from hepatocytes remain unknown. Methods Mice or primary hepatocytes were treated with APAP. APAP-AD were determined by immunoblot, immunostaining and HPLC-ED analysis. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 37 publications
6
151
2
Order By: Relevance
“…Under some conditions autophagy exerts protective effects to promote cell survival, while under some other conditions autophagy is detrimental to the cell (24,28,33). Previous reports showed that in hepatotoxic models induced by acetaminophen and ethanol, induction of autophagy was protective and inhibition of autophagy was detrimental (5,20,26,27). Consistent with these reports, in our study we found that autophagy enhancement by 3-MA pro- subsequent production of pro-inflammatory cytokine, IL-1β.…”
Section: Discussionsupporting
confidence: 91%
“…Under some conditions autophagy exerts protective effects to promote cell survival, while under some other conditions autophagy is detrimental to the cell (24,28,33). Previous reports showed that in hepatotoxic models induced by acetaminophen and ethanol, induction of autophagy was protective and inhibition of autophagy was detrimental (5,20,26,27). Consistent with these reports, in our study we found that autophagy enhancement by 3-MA pro- subsequent production of pro-inflammatory cytokine, IL-1β.…”
Section: Discussionsupporting
confidence: 91%
“…Both damaged mitochondria (Ni et al, 2012a) and protein adducts (Ni et al, 2016) were shown to be removed by autophagy, an adaptive mechanism that protects against APAP hepatotoxicity. The consistently lower adducts in C57BL/6J mice could be caused by the reduced formation of adducts compared to C57BL/6N mice or could be the result of higher autophagic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been thought to play a protective role against APAP hepatotoxicity through the removal of damaged organelles and alleviation of oxidative stress, and pharmaceutical inhibition of autophagy by leupeptin or chloroquine would render hepatocytes more sensitive to APAP‐induced necrotic cell death . Consistent with these findings, depletion of autophagy‐related gene Atg7 or SQSTM1/p62 in the liver strongly exaggerates AILI . However, probably attributed to the multiple functions of different autophagy‐related genes besides their roles in autophagy, liver‐specific knockout of Atg5 induced a paradoxically reduced liver injury during APAP treatment, which may be caused from a persistent activation of the Nrf2 antioxidant signaling pathway and increased hepatocyte proliferation during Atg5 loss …”
Section: Discussionmentioning
confidence: 79%